2012
DOI: 10.1152/jn.00853.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tonic GABAA receptor conductance in medial subnucleus of the tractus solitarius neurons is inhibited by activation of μ-opioid receptors

Abstract: Herman MA, Gillis RA, Vicini S, Dretchen KL, Sahibzada N. Tonic GABA A receptor conductance in medial subnucleus of the tractus solitarius neurons is inhibited by activation of -opioid receptors. J Neurophysiol 107: 1022-1031, 2012. First published November 23, 2011; doi:10.1152/jn.00853.2011.-Our laboratory previously reported that gastric activity is controlled by a robust GABA A receptor-mediated inhibition in the medial nucleus of the tractus solitarius (mNTS) (Herman et al. 2009), and that -opioid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In addition, MOR activation in this region has a powerful effect on vago-vagal reflexes controlling gastric function and tone. Interestingly, a recent study (Herman et al 2012) demonstrated gastric effects due to interactions between the manipulation of cNST -opioid and GABAergic receptors consistent with effects on cNST neurons observed in vitro (Herman et al 2010). …”
supporting
confidence: 59%
See 1 more Smart Citation
“…In addition, MOR activation in this region has a powerful effect on vago-vagal reflexes controlling gastric function and tone. Interestingly, a recent study (Herman et al 2012) demonstrated gastric effects due to interactions between the manipulation of cNST -opioid and GABAergic receptors consistent with effects on cNST neurons observed in vitro (Herman et al 2010). …”
supporting
confidence: 59%
“…DAMGO was bath applied to each cell at 0.3 M for 5.5 min, followed by a washout period in normal ACSF. This concentration fell in the middle of the range of concentrations reported in the literature (Herman et al 2012;Poole et al 2007;Rhim et al 1993;Rhim and Miller 1994) and was ideal for our purposes because in most cases it caused considerable but incomplete suppression of the evoked response, which allowed us to measure a PPR throughout the protocol. One of three baseline drug conditions was used: normal ACSF as described above, normal ACSF containing 5 M gabazine and 5 M strychnine, or normal ACSF containing gabazine, strychnine, and 1 M CTAP, a MOR antagonist (Glatzer et al 2007;Glatzer and Smith 2005).…”
Section: Methodsmentioning
confidence: 98%
“…Codeine and other agonists of μ-opioid receptors may mediate neuronal inhibition in the several subdivisions of the NTS (Poole et al, 2007) by both pre- and post-synaptic mechanisms (Endoh, 2006; Ohi et al, 2007; Boxwell et al, 2013) including modulation of glutamatergic neurotransmission (Andresen et al, 2013) and local GABA activity (Herman et al, 2012). The antitussive activity of codeine in cat is likely mediated also via non-opioid receptor mechanisms (Nosalova, 1998; for the discussion see Poliacek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential source of GABAergic influence may be the AMG. While anatomical evidence suggests that AMG input to the NTS is inhibitory Saha et al, 2002), physiological studies suggest that the effect of stimulation of AMG-NTS input is excitatory (Cho et al, 2003), suggesting the possibility that the AMG generates a disinhibitory effect in the NTS (see Herman et al, 2012). If true, that might contribute to the enhanced responses that became apparent following optical stimulation of GABA release.…”
Section: Discussionmentioning
confidence: 99%